Enhancing the surface strength of magnesium alloy AZ80 through cavitation peening - Sebastjan Žagar; Hitoshi Soyama; Boštjan Markoli; Iztok Naglič; Roman Šturm (Materials & Design)
In this study, the effects of cavitation peening on the surface properties of artificially aged Mg alloy AZ80 are investigated, focusing on surface roughness, microhardness, residual stresses and microstructure. The analysis by optical microscopy, scanning electron microscopy and backscattered electron diffraction shows that roughness, hardness and modified depth increase with increasing number of cavitation peening scans. The surface roughness (Ra) increased from 0.2 μm in the base material to 5.6 μm after cavitation peening of 20 scans (CP-20). The microhardness also increased from 80 HV0.05 to 112 HV0.05 at the same specimen. The compressive residual stresses improved from −10 MPa in the base material to −220 MPa after 5 scans (CP-5). With further increasing number of scans, residual stresses decreased to −20 MPa at 20 scans (CP-20). The microstructural analysis revealed that the increased occurrence of twins under the peened surface correlates with the decrease in compressive residual stresses. This indicates that excessive cavitation peening leads to twin formation and compressive stress loss. Therefore, limiting the number of scans is crucial for maintaining high compressive residual stresses level. At this point, the optimum number of cavitation peening scans for the material used has been suggested.